Intersection theory, relative cohomology and the Feynman parametrization - Mingming Lu; Ziwen Wang; Li Lin Yang (Journal of High Energy Physics)
Abstract We present a novel approach for loop integral reduction in the Feynman parametrization using intersection theory and relative cohomology. In this framework, Feynman integrals correspond to boundary-supported differential forms in the language of relative cohomology. The integral reduction can then be achieved by computing intersection numbers. We apply our method in several examples to demonstrate its correctness, and discuss the subtleties in certain degenerate limits.